2004
DOI: 10.1051/apido:2004010
|View full text |Cite
|
Sign up to set email alerts
|

The biology of the small hive beetle (Aethina tumida, Coleoptera: Nitidulidae): Gaps in our knowledge of an invasive species

Abstract: -Small hive beetles, Aethina tumida, are honeybee parasites native to Africa, where they are a minor pest only. In contrast, the beetles can be harmful parasites of European honeybee subspecies. Resistance of African subspecies to infestations is probably due to quantitative differences in a series of behaviours such as absconding, aggression, removal of parasite eggs and larvae and social encapsulation. The beetles use counter-resistance tactics such as defence posture, dropping, hiding, escape, egg laying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
298
0
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 203 publications
(320 citation statements)
references
References 42 publications
5
298
0
17
Order By: Relevance
“…In North Africa, the introduction of SHB into Egypt did not have significant negative impacts, and SHB populations remain low (El-Niweiri et al 2008) or absent (Hassan and Neumann 2008) in local honeybee colonies. Devastating effects have been reported in countries outside of Africa (Australia and the USA) where the beetles have been introduced (Neumann and Elzen 2004). From an African perspective, the beetles do not seem to pose a significant threat to beekeeping; however, the fact that they can act as vectors of honeybee viruses and bacteria should be of concern (Eyer et al 2009;Schäfer et al 2010).…”
Section: Coleoptera (Beetles)mentioning
confidence: 99%
“…In North Africa, the introduction of SHB into Egypt did not have significant negative impacts, and SHB populations remain low (El-Niweiri et al 2008) or absent (Hassan and Neumann 2008) in local honeybee colonies. Devastating effects have been reported in countries outside of Africa (Australia and the USA) where the beetles have been introduced (Neumann and Elzen 2004). From an African perspective, the beetles do not seem to pose a significant threat to beekeeping; however, the fact that they can act as vectors of honeybee viruses and bacteria should be of concern (Eyer et al 2009;Schäfer et al 2010).…”
Section: Coleoptera (Beetles)mentioning
confidence: 99%
“…In our laboratory experiments, this amount was achieved with the highest dosage of 50 mg after 72 h. In V. destructor treatments, the essential oil is usually applied in long-term treatments of 2 to 4 weeks (Imdorf et al 1999;Floris et al 2004). However, a bee colony can either be heavily infested with or even be killed by SHBs within 4 weeks (Elzen et al 1999;Neumann and Elzen 2004). Furthermore, Ellis and Delaplane (2006) showed that the thymolbased product Apilife Var™ had no effect on the host-finding ability of adult SHBs.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…For example, in the laboratory, the beetles were exposed to the agents without any hiding places. In contrast, eggs laid in crevices or in capped brood cells (Ellis et al 2003;Neumann and Elzen 2004;Spiewok et al 2007), as well as larvae that mine within combs (Lundie 1940;Schmolke 1974), are likely to be less exposed to the treatments. A high portion (>50%) of the introduced adult SHBs could not be relocated in the colonies neither in longer-term trials (e.g., 13 days in the formic acid investigation) nor in shorter trials (e.g., 48 h in the oxalic acid investigation).…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased international plant trade is considered as a major mechanism of pest dispersal with numerous pests and diseases being spread around the world (Lenteren and Woets, 1988;Neumann and Elzen, 2004). Within the European Union, a legislation exists that prohibits the movement of specific organisms of plant health importance (Anonymous, 2000;Bartlett, 1993;Cheek and Cannon, 2002).…”
Section: Introductionmentioning
confidence: 99%